The speech therapist advisory role: some considerations on collaborative consulting in regular school - Andréa Carla Machado; Suzelei Faria Bello; Maria Amelia Almeida (Universidade Federal de Santa Maria (UFSM), 2012)
The collaborative consulting system is a work possibility to collaborate and cooperate with the various protagonists in the educational system: school, teachers, family and the specialist consultant, who intends to meet the new demand of the inclusive process of the 21th century. The collaborative consulting is a proposal in which the professionals that are involved reflect together to solve the problems of the classroom. By considering that the speech therapist is intrinsically involved with the educational context and works with children with difficulties in oral communication, writing, voice and hearing, this study aimed at evaluating the effectiveness of phonoaudiologic cooperation with a collaborative perspective in school context. This is a questionnaire-intervention-questionnaire research for teachers before and after intervention. The proposal of Collaborative Consulting in educational context improved the collaborative process and became constructive with the various educational demands and gave the teacher safety and support in the continuous practice of the classroom, offering reflections which maximize the potential of each child and meet their diversity.